Updated report on tools to measure outcomes of clinical trials in fragile X syndrome - Dejan B. Budimirovic (Journal of Neurodevelopmental Disorders, 2017)
Abstract Objective Fragile X syndrome (FXS) has been the neurodevelopmental disorder with the most active translation of preclinical breakthroughs into clinical trials. This process has led to a critical assessment of outcome measures, which resulted in a comprehensive review published in 2013. Nevertheless, the disappointing outcome of several recent phase III drug trials in FXS, and parallel efforts at evaluating behavioral endpoints for trials in autism spectrum disorder (ASD), has emphasized the need for re-assessing outcome measures and revising recommendations for FXS. Methods After performing an extensive database search (PubMed, Food and Drug Administration (FDA)/National Institutes of Health (NIH)’s www.ClinicalTrials.gov , etc.) to determine progress since 2013, members of the Working Groups who published the 2013 Report evaluated the available outcome measures for FXS and related neurodevelopmental disorders using the COSMIN grading system of levels of evidence. The latter has also been applied to a British survey of endpoints for ASD. In addition, we also generated an informal classification of outcome measures for use in FXS intervention studies as instruments appropriate to detect shorter- or longer-term changes. Results To date, a total of 22 double-blind controlled clinical trials in FXS have been identified through www.ClinicalTrials.gov and an extensive literature search. The vast majority of these FDA/NIH-registered clinical trials has been completed between 2008 and 2015 and has targeted the core excitatory/inhibitory imbalance present in FXS and other neurodevelopmental disorders. Limited data exist on reliability and validity for most tools used to measure cognitive, behavioral, and other problems in FXS in these trials and other studies. Overall, evidence for most tools supports a moderate tool quality grading. Data on sensitivity to treatment, currently under evaluation, could improve ratings for some cognitive and behavioral tools. Some progress has also been made at identifying promising biomarkers, mainly on blood-based and neurophysiological measures. Conclusion Despite the tangible progress in implementing clinical trials in FXS, the increasing data on measurement properties of endpoints, and the ongoing process of new tool development, the vast majority of outcome measures are at the moderate quality level with limited information on reliability, validity, and sensitivity to treatment. This situation is not unique to FXS, since reviews of endpoints for ASD have arrived at similar conclusions. These findings, in conjunction with the predominance of parent-based measures particularly in the behavioral domain, indicate that endpoint development in FXS needs to continue with an emphasis on more objective measures (observational, direct testing, biomarkers) that reflect meaningful improvements in quality of life. A major continuous challenge is the development of measurement tools concurrently with testing drug safety and efficacy in clinical trials.